What forms can do : the work of form in 20th- and 21st- century French literature and thought - Crowley, Patrick; Jordan, Shirley (Contemporary French and francophone cultures., 2020)
How does form propose a bridge between the text and the world beyond? This volume investigates the agency of form across a spectrum of twentieth- and twenty-first century French and Francophone writings, renewing the engagement with form that has been a key feature of French cultural production and of analysis in French studies.